2020
DOI: 10.17085/apm.2020.15.2.251
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal compartment syndrome caused by gastric distension in bulimia nervosa and fatal injury following surgical decompression - A case report -

Abstract: Background: Abdominal compartment syndrome (ACS) occurs due to increased abdominal cavity pressure, causes multiple organ damage, and leads to fatal consequences. Increased intraperitoneal pressure due to different reasons generally does not result in serious damage, due to the compliance of the abdominal wall. However, when the pressure exceeds the limit, ACS develops, thereby causing fatal damage to the organs. Case: A patient presented with rapid stomach swelling due to excessive food intake and was known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This may be indicative and likely for translation, as reperfusion syndrome in patients can frequently occur during decompression surgery and be a cause of death. It was claimed that no therapeutic approach could improve the progression of the syndrome by itself [65][66][67][68]. On the other hand, the cytoprotection background and maintenance and/or recovery of endothelium function [1][2][3][30][31][32][33][34] in favor of this study (reperfusion-induced vascular and multiorgan failure, and occlusion/occlusion-like syndrome as a whole, strongly counteracted by BPC 157 therapy) provided a large beneficial range of effects of BPC 157 therapy that can be likely extended from the previous studies [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be indicative and likely for translation, as reperfusion syndrome in patients can frequently occur during decompression surgery and be a cause of death. It was claimed that no therapeutic approach could improve the progression of the syndrome by itself [65][66][67][68]. On the other hand, the cytoprotection background and maintenance and/or recovery of endothelium function [1][2][3][30][31][32][33][34] in favor of this study (reperfusion-induced vascular and multiorgan failure, and occlusion/occlusion-like syndrome as a whole, strongly counteracted by BPC 157 therapy) provided a large beneficial range of effects of BPC 157 therapy that can be likely extended from the previous studies [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…With conceptual notification that vascular rescue rapidly occurs in cytoprotection [36], the significance appears consistently [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. This would be prompt counteraction with rapid vessel recovery, ensuring the prompt capability of the vessels to take full blood flow and avoid (or stop) an otherwise imminent course (increased permeability, massive hemorrhage leading hypotension, cardiac failure, and arrhythmias) resulting in high mortality in patients [65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Most prior studies of the progression of AGD to ACS have reported unfavorable outcomes. [9,[19][20][21] Decompression is insufficient in cases where the food materials or other particles inside the stomach are larger than the hole at the tip of the NG tube. Autopsy studies have revealed that gastric volvulus or direct compression of the upper GI tract by the distended stomach is a crucial cause of death in ACS with AGD.…”
Section: Discussionmentioning
confidence: 99%